Principal Policy Analysis in The Management of Distance Learning in The Covid-19 - Haekal, T. M.; W, Sulaiman; Hafiz, Abdul; Cakranegara, Pandu Adi; Surahman, Susilo (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study examines the principal's policy in managing learning during the COVID-19 pandemic in schools. This study uses a qualitative type of field research. Madrasah principals, teachers, and committees are the primary data sources. Meanwhile, secondary data sources are obtained from relevant journals, books, magazines. The location of this research is Madrasah Ibtidaiyah Negeri 1 Malang. The findings of this study state that distance learning and problems during the Covid-19 period and analysis of basic policies by madrasah principals in managing distance learning with distance learning outcomes during the COVID-19 pandemic include policy analysis regarding student needs the use of learning applications. Evaluation activities and policies in the online learning process will be used. The importance of this research will be to provide solutions in learning to regulate flexibility in choosing a curriculum that is by the learning needs of students during the pandemic, as stipulated in the Decree of the Minister of Education and Culture related to the curriculum during an emergency.